Chemical Constituents and Biological Activities of Micromelum Minutum (Rutaceae) and Two Eugenia Species (Myrtaceae) - Susidarti, Ratna Asmah (2003)
Drug discovery has been a goal of mankind since prehistoric times. Plants continue to be an exceptionally viable source of biologically active natural products. However, only small portion of the higher plants has been phytochemically and pharmacologically investigated. Two separate collections of Micromelum minutum from Sabah and two Eugenia species, E. chlorantha and E. cumingiana collected from the northern forest of Perak were subjected to phytochemical investigation with the isolation of a number of compounds. The structures of these compounds were elucidated by using spectroscopic methods such as IR, UV, NMR, MS and also by comparison with previous reports. The crude extracts, essential oil and isolated compounds from these plant materials were evaluated for their antiinflammatory, cytotoxic and antimicrobial activities using carrageenan-induced rat paw oedema, MTT and disc diffusion methods, respectively. Some isolated compounds showed interesting biological activities.